Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/antibiotics10030332
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes and Practices Regarding Antibiotic Use and Resistance among Veterinary Students in Bangladesh

Abstract: The use of antibiotics in animals for both therapeutic and non-therapeutic purposes is a major driver of the emergence and spread of antimicrobial resistance (AMR). While several studies have investigated prescription and consumption patterns in humans, little attention has been paid to the veterinary sector. A cross-sectional study was conducted in 3002 veterinary students (VS) and non-medical students (NMS) from 12 universities in Bangladesh to explore their knowledge, attitudes and practices (KAP) about ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 30 publications
(70 reference statements)
1
19
0
Order By: Relevance
“…Some research also showed that one-on-one meetings, with the dissemination of resource materials, were positively associated with changing farmers’ behavior regarding AMR [ 42 ]. In alignment with other studies, [ 42 , 43 , 49 ], the current investigation showed that the level of education, experience, and training on AMU and AMR, not only for veterinarians but also for other animal health workers, could be crucial in altering the prescribing behavior of farmers.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Some research also showed that one-on-one meetings, with the dissemination of resource materials, were positively associated with changing farmers’ behavior regarding AMR [ 42 ]. In alignment with other studies, [ 42 , 43 , 49 ], the current investigation showed that the level of education, experience, and training on AMU and AMR, not only for veterinarians but also for other animal health workers, could be crucial in altering the prescribing behavior of farmers.…”
Section: Discussionsupporting
confidence: 83%
“…Lack of facilities for ASTs and the higher cost associated with existing AST facilities in the country, leading to their lack of affordability for farmers, might be the factors leading to not ordering ASTs in the selection of antimicrobials, as described in the literature [ 48 ]. These factors may further lead to inappropriate use of antimicrobials in terms of using additional antimicrobials in a single prescription, or overdosing of antimicrobials [ 49 , 50 ]. However, veterinarians overcome these limitations by using their own experience, sharing the experience of senior colleagues, previous training, and gathering information from different sources, and this was also supported by the findings of other studies [ 42 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, such study is still lacking from Bangladesh. In Bangladesh, the KAP regarding antibiotic use and resistance among veterinary students has been reported previously [21]. Therefore, in this study, we have explored the KAP of the veterinarians of Bangladesh regarding antibiotic use and resistance.…”
Section: Introductionmentioning
confidence: 95%
“…On the other hand, such study is still lacking from Bangladesh. In Bangladesh, the KAP regarding antibiotic use and resistance among veterinary students has been reported previously [21].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study on about 3000 veterinary students showed gaps in knowledge and practices concerning antibiotic resistance. These gaps will likely contribute to inadequate use in their future practice and to the release of antibiotics into the environment [ 35 ].…”
Section: Activities For Medical Studentsmentioning
confidence: 99%